Partisipasi Tokoh Masyarakat dalam Pembangunan di Desa Terasa Kecamatan Sinjai Barat Kabupaten Sinjai - Hamdan Hamdan; Supratman Tahir; Muhammad Amar (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this research is that the role of the village government in the implementation of development is still relatively weak, even if it does not seem to function in mobilizing the community to participate in village infrastructure development. Some village infrastructure is damaged, but the main problem of Terasa Village is the uneven development of road infrastructure. So it needs serious handling from the village government. The sustainability of village development is inseparable from the role of the community as well as the leadership of the village head, and village officials. Where the role of village officials and the community is very important in village development. In reality, most people in Terasa Village do not feel the benefits of the development. Especially in the development of road infrastructure, the condition of Terasa Village roads is very concerning. The road is filled with puddles and scattered coral stones. Until now, roads have not been paved, road infrastructure development is only casted and does not last long because the construction seems careless so that within a month, two months the castings are damaged again, uneven development, one road is divided in two and the middle is vacated.